A search for new phenomena in pp collisions at root s=13TeV in final states with missing transverse momentum and at least one jet using the alpha(T) variable - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (European Physical Journal C, 2017)
A search for new phenomena is performed infinal states containing one or more jets and an imbalance intransverse momentum in pp collisions at a centre-of-massenergy of 13 TeV. The analysed data sample, recorded withthe CMS detector at the CERN LHC, corresponds to an inte-grated luminosity of 2.3 fb−1. Several kinematic variablesare employed to suppress the dominant background, mul-tijet production, as well as to discriminate between otherstandard model and new physics processes. The search pro-vides sensitivity to a broad range of new-physics models thatyield a stable weakly interacting massive particle. The num-ber of observed candidate events is found to agree with theexpected contributions from standard model processes, andthe result is interpreted in the mass parameter space of four-teen simplified supersymmetric models that assume the pairproduction of gluinos or squarks and a range of decay modes.For models that assume gluino pair production, masses up to1575 and 975 GeV are excluded for gluinos and neutralinos,respectively. For models involving the pair production of topsquarks and compressed mass spectra, top squark masses upto 400 GeV are excluded.